2015
DOI: 10.1002/zoo.21249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental enrichment and stereotypic behavior on maternal behavior and infant viability in a model carnivore, the American mink (Neovison vison)

Abstract: In several species, stress compromises maternal behaviors that are important for infant viability (e.g. licking and grooming). Understanding how stress in captivity affects maternal behavior could therefore be beneficial, especially for carnivores in zoos and breeding centers where infant mortality is often high. We used a model carnivore--American mink--to test two hypotheses, namely that maternal investment and/or behavior is i. improved by environmental enrichment; and ii. compromised by stereotypic behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Zoo animal welfare is one of the key components in modern zoos achieving their aims (conservation, education, research and recreation). For example, with low welfare standards, an animal’s reproductive success decreases [ 7 , 8 ]. Godinez et al [ 9 ] also found that increases in animal stereotypies decreased visitor enjoyment, reducing the zoo’s opportunities to contribute towards both in situ and ex situ conservation strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zoo animal welfare is one of the key components in modern zoos achieving their aims (conservation, education, research and recreation). For example, with low welfare standards, an animal’s reproductive success decreases [ 7 , 8 ]. Godinez et al [ 9 ] also found that increases in animal stereotypies decreased visitor enjoyment, reducing the zoo’s opportunities to contribute towards both in situ and ex situ conservation strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…But mink also show an idiosyncratic scrabbling or digging with the forepaws. Unlike loco SB, this sub-type of SB is not Carnivora-typical; is unrelated to perseveration [42]; is elicited by the proximity of neighbours [64]; does not predict failure in mating competitions [65]; and is not reduced long-term by enriched-rearing, if enriched-raised mink are transferred to barren conditions [59].…”
Section: Introductionmentioning
confidence: 95%
“…Briefly, the NE environments consisted of a wire mesh home cage (61x76x46cm) with an attached nestbox (bedded year round). E environments consisted of this basic home cage with a series of overhead structures (including ramps to climb up and down and a 2.5m tunnel) providing each animal with free access to an extra compartment double the size of his home cage, and containing an extra nestbox, a swing, circulating water in which to wade, and several manipulable objects, some familiar, some new each month [60,65]. These E conditions are preferred by mink [10] and reduce their physiological stress [59].…”
Section: Subjects and Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…The early detection of other progressive conditions such as renal failure also allows for medical and husbandry interventions designed to slow deterioration, to be put in place, thereby maximising both quality and quantity of life. Any improvement to animal health and welfare is also likely to have a positive impact on breeding success [41,42] and, by encouraging more species-specific natural behaviours, might also enhance visitor perception and experience [43].…”
Section: Health Check Outcomesmentioning
confidence: 99%